A Review on Bioactive Compounds and Pharmacological Properties of Cleome rutidosperma DC: A review on Cleome rutidosperma - Nguyen, Trang (Journal of Tropical Life Science, 2023)
Cleome rutidosperma DC., a species of flowering plant in the Cleomaceae family, is commonly known as "fringed spider flower" or "purple cleome". It is distributed in the tropical and subtropical regions of Asia and Africa. The plant species is widely utilized in folk medicinal practices. According to traditional medicinal reports, the plant has been used to alleviate pain, spasms, and skin diseases, as well as to reduce symptoms of deafness, earaches, and convulsions. This study aims to consolidate the available information on traditional medicine, botanical aspects, phytochemistry, and pharmacology of C. rutidosperma. Published articles on this species since 2000 were comprehensively analyzed. Databases, such as Google Scholar, Scopus, ScienceDirect, and PubMed, were employed. Pharmacological studies have demonstrated that C. rutidosperma possesses various bioactivities, including analgesic, anti-inflammatory, antidiabetic, and anticancer effects. Multiple phytochemicals have been identified in the plant. These phytoconstituents could contribute to the high antioxidant properties and multiple bioactivities of C. rutidosperma that hold great potential for human health